Naming is power! Black and white adolescents define sexual coercion: A mixed methods study - French, Bryana H. (2010)
This study sought to explore adolescent conceptualizations of sexual coercion (i.e., any unwanted sexual experience) among Black and White girls and women. Adolescents are at significant risk for sexual coercion with over 50% of sexual assault survivors between the ages of 12 and 20 (Catalano, 2005). Smaller studies suggest that nonviolent sexual coercion (e.g., verbal pressure, substance use) occurs more frequently than the threat or use of force (Basile, 2002; Spitzberg, 1999; Poitras & Lavoie, 1995), and are related to deleterious mental health outcomes (e.g., increased depression, lowered self-esteem; Broach & Petretic, 2006; Cecil & Matson; French & Neville, 2008; Testa & Dermen, 1999). Despite existing sexual coercion knowledge, much of the existing research relies primarily on adult White samples Thus, there is a paucity of research on Black adolescent perceptions of sexual coercion. Given the pervasive nature of sexual coercion, its harmful influence on Psychological adjustment, limited research on Black populations, and the overrepresentation of adolescents in sexual Victimization, continued research is needed to examine the breadth of adolescent sexual coercion from racially diverse perspectives. Sexual violence scholars have advocated for research that uncovers socially constructed definitions to acknowledge differences in cultural realities (Kelly & Radford, 1998; Muehlenhard & Kimes, 1999). Thus, this study uses a social constructionist, mixed methods approach to explore the sexual coercion conceptualizations of Black and White girls and women. Openended responses and survey data with 256 Black and White high school and college women were qualitatively analyzed for themes and statistically analyzed using logistic regression to explore relations between responses, race, grade level, and sexual coercion history. Data from 3 semistructured focus groups with high school and college women were analyzed using thematic and dimensional analyses to explore the subjective realities ...